Вольному-воля - Колычев Владимир Григорьевич (Русский шансон, 2008)
Экземпляры: ф-21 (20200811) / Инвентарный номер: 55706 / Цена: 60.00 / Сис.шифр: Р2 / Авт.знак: К 61 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6